Selection a suitable supplier for enhancing supply chain management under neutrosophic environment - Hager Hosny; Ibrahim El-Henawey; Samah Abo-El-Hadid (Neutrosophic Sets and Systems, 2021)
In supply chain management (SCM), selecting a sustainable supplier has improved as one of the most urgent issues. Several previous research has attempted to determine how to choose a sustainable supplier using various strategies and approaches. A suitable supplier needs to be chosen to improve the quality of products, services, reduce prices of purchasing, and regulate time. This paper aims to Enhance Supply Chain Management for the Suitable Supplier selection by integrating the neutrosophic Analytical Hierarchy Process (AHP) with Multiplicative Multi-Objective Optimization based on Ratio Analysis (MULTIMOORA) approach. Furthermore, this is a Multi-Criteria Decision-Making (MCDM) issue, selecting sustainable providers is complex. because includes unclear information, decision-makers' loss of accuracy, indeterminate, uncertainty, and inconsistent information. For this, we use a single value neutrosophic set (SVNS) to can handle unclear information, the knowledge that is inaccurate, and indeterminate, uncertain information. The proposed study applies integrating Single Valued Neutrosophic AHP for calculating the weights of different criteria taking into account their interdependencies. Then the MULTIOORA technique ranks the different alternatives, then chooses the best provider. A case study is utilized on the pharmaceutical manufacturing company. The case study uses the integrated approach to analyze and choose the ideal supplier.